A Study on E-services Introduced During the COVID-19 Pandemic by Kelaniya University Library - Somananda Thero, B. (Department of Library and Information Science, University of Kelaniya, Sri Lanka, 2023)
University libraries have a unique place in teaching and research activities. Due to the COVID-19 epidemic, the fulfillment of educational needs and maximum support to users through university libraries has been hindered, as most activities were paralyzed. As a result, e-services such as Digital Repositories, Past Paper Repository, Subject Liaison, Library Services (SLLS), Chat Services, Audio Book Collection, Braille Collection, Mobile App, Webinar Series have been established as challenges to the COVID-19 epidemic. The case study research method was used for this research, and for data collection, users of the University of Kelaniya were taken as the entire population, and data was collected from all the students. Online questionnaire-interview methods were used for data collection. In focusing on the use of electronic library services by Kelaniya University students, it was possible to identify the lack of awareness of the use of electronic services and those services as a major problem. Also, the inability to use the mobile app for some phones, the non-functionality of some programs, the nonimplementation of reader education programs on new electronic programs started with the spread of the COVID-19 epidemic, and the non-availability of books in electronic form as required by each subject, as well as other problems, were possible. The library already has a mobile app. Taking the department as a whole to carry out awareness programs about electronic services in the library through librarians, implementing information delivery services for students who do not have internet facilities, and starting courses for readers that include the English and computer knowledge required to use library electronic services have been suggested. keywords: Library, University Library, Covid-19, Library Services, Electronic Library Services
Keywords: Library, University Library, Covid-19, Library Services, Electronic Library Services